(A study of Yoghurt Processing from Soybean Flour) - Sutrisniati, Dwi; Bowolimawan, Susilo; Wiriano, Harry (Warta Industri Hasil Pertanian, 1991)
Yogurt was made from soy milk which was prepared from soybean flour, added with skim milk (3%, 4%, and 5%), and fermented at 42 derajat - 44 derajat celcius for 3 hours using Lactobacillus bulgaricus and streptococcus thermophilus as starters (1% : 1% : 1.5% : 1% and 2% : 1%). The products were evaluated for its pH, total soluble solid and organoleptic test. The increasing addition of skim milk resulted in the decreasing of pH, while the total soluble solid and organoleptic test score increased. The most acceptable product was made with the addition of 5% skim milk and 2.5% starter of L. bulgaricus and S. thermo-philus (1.5 : 1).